2005
DOI: 10.1161/01.str.0000166181.86928.8b
|View full text |Cite
|
Sign up to set email alerts
|

Refining the Perfusion–Diffusion Mismatch Hypothesis

Abstract: Background and Purpose-The Echoplanar Imaging Thrombolysis Evaluation Trial (EPITHET) tests the hypothesis that perfusion-weighted imaging (PWI)-diffusion-weighted imaging (DWI) mismatch predicts the response to thrombolysis.There is no accepted standardized definition of PWI-DWI mismatch. We compared common mismatch definitions in the initial 40 EPITHET patients. Methods-Raw perfusion images were used to generate maps of time to peak (TTP), mean transit time (MTT), time to peak of the impulse response (Tmax) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
193
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(197 citation statements)
references
References 27 publications
2
193
2
Order By: Relevance
“…This is a relevant finding taking into account that a volumetric difference of 20% between DWI and PWI volume is commonly postulated for mismatch definition. 4,7,10,11,48 This methodical problem has already been addressed in previous ROI-based studies of a small patient sample 39,42 and in healthy volunteers. 38 These studies, like in our sample, found good agreement of ROI values on an individual basis.…”
Section: Zaro-weber Et Al Mri-cbf In Acute Stroke Compared With H 2 Omentioning
confidence: 99%
See 1 more Smart Citation
“…This is a relevant finding taking into account that a volumetric difference of 20% between DWI and PWI volume is commonly postulated for mismatch definition. 4,7,10,11,48 This methodical problem has already been addressed in previous ROI-based studies of a small patient sample 39,42 and in healthy volunteers. 38 These studies, like in our sample, found good agreement of ROI values on an individual basis.…”
Section: Zaro-weber Et Al Mri-cbf In Acute Stroke Compared With H 2 Omentioning
confidence: 99%
“…Most studies used time-to-peak (TTP) or mean transit time maps for mismatch calculation because these parameters are robust and easy to obtain. [7][8][9][10][11][12][13] The MRI-based measurement of cerebral blood flow (CBF MRI ), although considered a close estimate of cerebral perfusion, 14 was applied in only few clinical studies. 13,[15][16][17][18][19][20][21] CBF MRI was mainly described with respect to infarct development on follow-up MRI that suffered from the uncertainty of perfusion changes between early MRI and follow-up imaging.…”
mentioning
confidence: 99%
“…PWI shows the relative latency of arrival and clearance of blood flow to each voxel of the image. Areas of tissue with a time to peak arrival of contrast of > 4 seconds delay, relative to the homologous region in the contralesional hemisphere, are areas that may be getting enough blood to survive, but not enough to function correctly and can be considered "hypoperfused" (Barber, et al, 1998;Butcher et al, 2005;Hillis et al, 2001b). Therefore, tissue areas of dense ischemia and/or hypoperfusion can be considered dysfunctional.…”
mentioning
confidence: 99%
“…These mismatch patients are then seen as appropriate candidates for the more aggressive interventions (ie, late IV tPA or IA interventions). 34 Unfortunately, the 2 largest randomized trials to look at this issue with respect to >3-hour IV tPA both failed to show a benefit for patients selected in this manner. 35,36 Standardized definitions of ''mismatch'' are still needed, and larger randomized trials are needed before this approach can be suggested for routine care.…”
Section: No Blood On the Ct Scan Results Back In <3 Hours From Symptmentioning
confidence: 99%